UMP’s Mymohes data transmission awarded 5-star rating - UMP, PNC
Universiti Malaysia Pahang (UMP) was tops when it was awarded with a five-star rating for its 2010/2011 second semester data transmission via the Data Maintenance for Higher Education Ministry’s related Public Institutes of Higher Learning (IPTA) Information System (MyMohes) recently.